Physicochemical And Antibacterial Characteristics Of Citrus Essential Oil Nanoemulsions - Moyeen, Tahsina (Universiti Sains Malaysia, 2020)
The undertaking of food technologists to create natural preservatives has given essential oils a new limelight not only as a coveted ingredient of skincare products but also, as a strong antimicrobial and antioxidant agent to be incorporated in edible goods. A solution to the hurdle of creating a water based solution containing lipophilic essential oil is nanoemulsion technology, which can uniformly hydrophilize, disperse, and protect the essential oil molecules in the continuous aqueous phase. Essential oil nanoemulsions are oil in water (o/w) emulsions and the formulation ratio of each, consists of a greater portion of the continuous phase in comparison to the surfactant encapsulated dispersed lipid phase. In this study, previous researches which discussed the characteristics and investigated the functional properties of nanoemulsions made with citrus essential oils obtained from fruits of the Rutaceae family namely, calamansi lime (Citrofortunella microcarpa), kaffir lime (Citrus hystrix), lemon (Citrus limon) and orange (Citrus sinensis) were comprehensively compared to identify the parameters which controlled both the physical stability and antibacterial activity. The essential oil nanoemulsions were differentiated against one another on the basis of their physicochemical properties such as, particle size, particle size distribution, polydispersity index, turbidity, viscosity and zeta potential respectively.